Effects of Scaffolding and Conventional Instructional Methods on Female Students’ Academic Achievement and Mathematics Anxiety in Geometry - Manko Umar Ahmad; Aliyu Alhaji Zakariyya; Alhassan Dyadya Isa; Abubakar Sadiq Ndagara (Journal of Instructional Mathematics, 2024)
This study aimed to assess the effect of scaffolding and conventional instructional methods on female students’ academic achievement and mathematics anxiety in geometry. The study used a quasi-experimental pre-test and post-test control design. The population comprised 443 SSII female students from 8 public schools in Agaie, Niger State, Nigeria. A sample of 130 SSII students from two schools was selected through multistage sampling. Data were collected through four instruments: Scaffolding lesson model for the experimental group, Conventional lesson model for the control group, Geometry Achievement Test (GAT) and Mathematics Anxiety Questionnaire (MAQ). The instruments were validated by three experts from two University. The reliability index of GAT and MAQ are 0.76 and 0.86 respectively. Research questions were answered through mean (M), standard deviation (SD), and mean difference, while a t-test at 0.05 level of significance was used to analyze the null hypotheses. The findings revealed that female students exposed to the scaffolding instruction method have higher mean scores than those exposed to the conventional instructional method. Based on the results, it is recommended, among others, that teaching mathematics, especially geometry, incorporate scaffolding instruction. Similarly, this method should be incorporated into the methodology and micro-teaching courses of pre-service teachers.